Calcium at the Center of Cell Signaling: Interplay between Endoplasmic Reticulum, Mitochondria, and Lysosomes - Raffaello, Anna; Mammucari, Cristina; Gherardi, Gaia; Rizzuto, Rosario (Trends in biochemical sciences (Amsterdam. Regular ed.), 2016)
In recent years, rapid discoveries have been made relating to Ca2+ handling at specific organelles that have important implications for whole-cell Ca2+ homeostasis. In particular, the structures of the endoplasmic reticulum (ER) Ca2+ channels revealed by electron cryomicroscopy (cryo-EM), continuous updates on the structure, regulation, and role of the mitochondrial calcium uniporter (MCU) complex, and the analysis of lysosomal Ca2+ signaling are milestones on the route towards a deeper comprehension of the complexity of global Ca2+ signaling. In this review we summarize recent discoveries on the regulation of interorganellar Ca2+ homeostasis and its role in pathophysiology. Ca2+ signaling is regulated by the intimate interconnection between intracellular organelles and plasma membrane channels. The ultrastructures of endoplasmic reticulum and mitochondrial Ca2+ channels have been determined. Great advances have been made in our understanding of the function and regulation of the mitochondrial calcium uniporter. Studies on endolysosomal Ca2+ signaling unravel a potential contribution of this compartment to global Ca2+ homeostasis.